The Interplay Between Physical Fitness, Nutritional Status, and Academic Performance in Physical Education: A Systematic Review - Andi Ihsan; Andi Muhammad Fadlih; Muhammad Qasash Hasyim; Amirzan Amirzan (Physical Education Theory and Methodology, 2025)
Objectives. This review aimed to explore the extent to which physical fitness and nutritional status serve as significant predictors of learning outcomes in physical education (PE) among secondary school students. Given the growing concern about sedentary lifestyles and poor eating habits among teens, understanding these relationships is critical to improving physical and academic performance.